Implementation of the Caesar Chiper Method in Cryptography for Message Data Security - Hidayat, Muhammad Ferdiansyah; Ridho, Muhammad; Indra, Zulfahmi (CV. Rayyan Dwi Bharata, 2024)
Data security in the digital era is a very important aspect, especially in maintaining the confidentiality and integrity of information transmitted over the network. One of the classic cryptographic methods that is often used to secure messages is the Caesar Cipher. This method uses a simple substitution technique, where each letter in the message is shifted a certain number of steps in the alphabet. This research discusses the implementation of the Caesar Cipher method as a basic solution for message data security. Although this algorithm is relatively easy to implement and understand, the Caesar Cipher has weaknesses, mainly due to its fixed shifting pattern making it vulnerable to brute force attacks or frequency analysis. Through testing and implementation, this research shows how Caesar Cipher works in the encryption and decryption process, and evaluates its effectiveness in protecting messages from unauthorized access. The results show that this method, although less powerful than modern algorithms, can still be used for certain scenarios that do not require a high level of security. On the other hand, the weaknesses underscore the importance of developing and using more complex cryptographic methods to protect more sensitive information in today's digital era.